Overcompensation: a 30-year perspective - Satu Ramula; Ken N. Paige; Tommy Lennartsson; Juha Tuomi (WILEY, 2022)
Biomass removal by herbivores usually incurs a fitness cost for the attacked plants, with the total cost per unit lost tissue depending on the value of the removed tissue (i.e., how costly it is to be replaced by regrowth). Optimal defense theory, first outlined in the 1960s and 1970s, predicted that these fitness costs result in an arms race between plants and herbivores, in which selection favors resistance strategies that either repel herbivores through morphological and chemical resistance traits in order to reduce their consumption, or result in enemy escape through rapid growth or by timing the growth or flowering to the periods when herbivores are absent. Such resistance against herbivores would most likely evolve when herbivores are abundant, cause extensive damage, and consume valuable plant tissues. The purpose of this Special Feature is to celebrate the 30th anniversary of the phenomenon of overcompensation, specifically, where the finding has brought us and where it is leading us 30 yr later. We first provide a short overview of how the phenomenon of overcompensation has led to broader studies on plant tolerance to herbivory, summarize key findings, and then discuss some promising new directions in light of six featured research papers.